Menciptakan Iklim Sekolah Yang Positif Dan Mengembangkan Mental Generasi Muda - Saptaningtyas Dwi Pertiwi; Rizkya Dwijayanti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Education is essentially the foundation for each individual to develop and shape his personality and social identity. The actions or behaviors include disciplinary violations, plagiarism, cheating, bullying caused by students close to the teacher to the implementation of free schools for students close to the teacher. This study used a quantitative approach. The population in this study was all students from grades I to VI at SDN Rungkut kidul 1/267 Surabaya City as many as 381 students. This sampling uses a random sampling technique, which will later use the Slovin formula obtained 79 people. The results of the calculation F count of 14,768, the variable School Climate of 1,765, the variable of Mental Development of 2,570 and the value of the coefficient of determination (R2) of 0. 626 or 62.6% which means that the contribution to the school climate and mental development of the younger generation who attend SDN Rungkut kidul 1/267 Surabaya City is getting stronger